Lubok 5 - Ruckhäberle, Christoph; Siemon, Thomas (Leipzig : Lubok Verlag, 2008)
Robert Schmiedel, Spar, Gitte Bach, Jirka Pfahl, Simone Wassermann, Malene Hartmann, Tobia Lehner, Steve Viezens, Claus Stabe, Anke Theinert
Exemplar No.: 681/700
boek